Book Review: Managing Network Resources by Ranjay Gulati. (10th March 2009) - Chinta, Ravi
Managing Network Resources, by Ranjay Gulati. New York, Oxford University Press, 2007. 480pp. ISBN: 978-0-19-929935-5